Development Bigbook Global Method Based for Student Class 2 of SD Negeri 054892 Lau Gelugur - Della Puspita; Icha Fadillah Putri; Ninda Audiska (Journal of General Education Science, 2024)
Study This aim For develop bigbook based global method . Study This is research and development (R&D). Study This using a 4D development model . The 4D development model consists from a number of stages among them that is define, design , develop and disseminate. Study This only until in stage development. Study This held at SD Negeri 054892 Lau Gelugur , from October to December 2023. Subject study that is student class 2 with a total of 16 students , consisting of of 10 students boy and 6 students Woman . Object of research that is bigbook based global method . Data collection techniques , namely observation, tests and questionnaires . Based on results study is known that results validation developed products that is bigbook based global method viz results validation media expert with percentage 96.90% incl Very worthy category, results validation expert material with percentage 87.50% incl very worthy category, and results validation expert Language with percentage 90.46% incl Very worthy category. Based on description that, then can concluded that developed products that is bigbook based global methods are said to be very feasible For used student class II at SD Negeri 054892 Lau Gelugur.